Curriculum Merdeka Belajar Kampus Merdeka Planning Management System Components In Improving The Quality Of Graduates In Era 5.0 - Muhammad Iqbal; Muhammad Muhammad; Zaiturrahmi Zaiturrahmi (Jurnal Mamangan, 2022)
Management is a cooperative system that includes all components of an educational institution. The management framework needs to be mastered by education managers, from planning, organizing, implementing, evaluating, and monitoring, in order to run effectively and efficiently. Curriculum management plays a very important role in preparing the material taught by educators and students. The curriculum can be used as a measure of success and the quality of education. This study seeks to analyse and find the MB-KM curriculum planning in improving the quality of graduates at the Jabal Ghafur School of Health Sciences. This study uses a multi-case strategy. In-depth interviews, participant observation, and documentation collected data. Data reduction, presentation, validation, and reporting employ the Miles Huberman paradigm. Data from single-case and cross-case studies was analyzed. Data validation uses validity, portability, reliability, and verifiability. The results showed that curriculum planning in improving the quality of education was prepared using the MB-KM curriculum based on the vision and mission of the university and the Ministry of Education, Culture and Research.